SOCIAL STUDIES WITHIN TRANSDISCIPLINARY LEARNING : PREPARING STUDENTS ABILITY TO SUPPORT SUSTAINABILITY LIVING - Pratiwi, Sari (Universitas Pendidikan Indonesia, 2019)
Preparing the young for membership is a central function of education. For better or worse, education influences human perspectives, actions, and relationships. Social Studies learning is a scientific field that cannot be separated from its role in solving problems that occur in society. Students will participate as agents of change in society that have knowledge, insights, attitudes, and understandings that are upholding sustainability. However, social studies learning is considered to not be able to maximize its role in preparing students to have competencies to support sustainability. It has not been able to maximize the role of students in society, and social studies re hereditary and still considered an elusive and boring lesson. For this reason, social studies need more Authentic Learning, which simulates a real-world environment by making it a source and a medium of learning, so that the context and allowance are used with similar situations, meaningful and connected to the real world by applying transdisciplinary learning. This paper contains a literature review on the application of learning in social studies learning to prepare students to live in harmony with the sustainable living. This literature studies refer to the theoretical aspects of : transdisciplinary learning, social studies within transdisciplinary learning, and learning outcomes related to sustainable living.